Influence of concurrent chemotherapy on locoregionally advanced nasopharyngeal carcinoma treated with neoadjuvant chemotherapy plus intensity-modulated radiotherapy: A retrospective matched analysis - Wang, Fangzheng (Sci Rep, 2020)
Neoadjuvant chemotherapy (NAC) combined with intensity-modulated radiotherapy (IMRT) plus concurrent chemotherapy (CC) will be the new standard treatment for locoregionally advanced nasopharyngeal carcinoma (NPC) patients. However, many patients fail to receive CC for multiple reasons. We aimed to investigate long-term survival outcomes and toxicities in these patients with NPC treated with additional NAC plus concurrent chemoradiotherapy (CCRT) or IMRT alone. In total, 1,378 previously untreated, newly diagnosed locoregionally advanced NPC patients receiving NAC plus IMRT with or without CC were retrospectively reviewed. We used a propensity score-matched (PSM) method with 1:1 matching to identify paired patients according to various covariates. Survival outcomes and toxicities were compared between the two groups. In total, 288 pairs were identified. With a median follow-up of 86 (range: 8–110) months, the estimated 5-year locoregional relapse-free survival, distant metastasis-free survival, progression-free survival (PFS), and overall survival rates in patients treated with NAC plus CCRT vs. NAC plus IMRT alone were 96.1% vs. 94.7% (P = 0.201), 93.7% vs. 89.8% (P = 0.129), 91.3% vs. 85.1% (P = 0.024), and 93.0% vs. 90.6% (P = 0.362), respectively. Multivariate analysis showed that CC omission was a prognostic factor for worse PFS. In a subgroup analysis, PFS did not differ significantly between two groups of female patients or aged <60 years or stage T1–2 or stage N0-1 disease. However, fewer acute complications were observed in the NAC plus IMRT alone group. NAC with IMRT alone confers similar survival rates and less acute toxicities. Specifically, NAC plus IMRT alone may be enough for female patients <60 years with stage T1-2 or stage N0-1. However, a prospective randomised trial is needed to validate these results.